Developing Topic-specific Search Filters for PubMed with Click-through Data - Li, J.; Lu, Z. (Methods of Information in Medicine, 2013)
Objectives: Search filters have been developed and demonstrated for better information access to the immense and ever-growing body of publications in the biomedical domain. However, to date the number of filters remains quite limited because the current filter development methods require significant human efforts in manual document review and filter term selection. In this regard, we aim to investigate automatic methods for generating search filters.Methods: We present an automated method to develop topic-specific filters on the basis of users’ search logs in PubMed. Specifically, for a given topic, we first detect its relevant user queries and then include their corresponding clicked articles to serve as the topic-relevant document set accordingly. Next, we statistically identify informative terms that best represent the topic-relevant document set using a background set composed of topic irrelevant articles. Lastly, the selected representative terms are combined with Boolean operators and evaluated on benchmark datasets to derive the final filter with the best performance.Results: We applied our method to develop filters for four clinical topics: nephrology, diabetes, pregnancy, and depression. For the nephrology filter, our method obtained performance comparable to the state of the art (sensitivity of 91.3%, specificity of 98.7%, precision of 94.6%, and accuracy of 97.2%). Similarly, high-performing results (over 90% in all measures) were obtained for the other three search filters.Conclusion: Based on PubMed click-through data, we successfully developed a high-performance method for generating topic-specific search filters that is significantly more efficient than existing manual methods. All data sets (topic-relevant and irrelevant document sets) used in this study and a demonstration system are publicly available at http://www.ncbi.nlm.nih.gov/CBBresearch/Lu/downloads/CQ_filter/
Keywords: Information retrieval; PubMed search filter; PubMed log analysis; clinical topic